Settler society in the Australian colonies self-government and imperial culture - Woollacott, Angela 1955- (Oxford Oxford University Press, 2015)
A fresh look at the history of the Australian colonies from the 1820s to the 1860s, a foundational period when free settlers gradually overtook convicts, the colonies dramatically expanded their territorial control, and both settlers and officials saw the potential for changes in the ways in which the colonies were governed.
Includes bibliographical references and index.
Keywords: Electronic books; Australia -- History -- 1788-1851.; Australia -- Colonization; Great Britain -- Colonies -- Oceania